Attomolar sensitivity of a redox capacitive and DNA-receptive interface attained by quantum-rate signal amplification concept - Carr, Olivia [UNESP] (2025)
This study demonstrates the application of quantum capacitance (Cq) methods to develop highly sensitive genosensors. This is achieved by employing the quantum mechanical rate (ν∝e2/hCq) concept to enhance the signal response of a redox-active, DNA-receptive interface. In these DNA-receptive interfaces, electrons are transported through the redox-tagged component, enabling signal amplification by adding a redox probe to the sample containing the target DNA. This is effective provided the formal potential of the added redox probe aligns with the energy state E=e2/Cq of the redox-tagged interface. This signal amplification methodology allowed us to detect attomolar levels of DNA biomarkers for diagnosing head and neck squamous cell carcinomas, where amplification is advantageous due to the typically low concentrations of target DNA in biological samples. Designed redox-tagged and DNA-receptive interfaces exhibited a broad detection range, from 103 aM to 108 aM (without amplification) and 1 aM to 105 aM (with amplification), with limit-of-detections ranging from 1.5 fM (without amplification) to 2.2 aM (with amplification). This demonstrates the attomolar sensitivity of this quantum-mechanical signal amplification method for label-free and early clinical diagnosis of cancer, using a genomic receptive interface fabricated through well-established self-assembled monolayer approaches.